Balanced Scorecard Evaluation of the Performance of Indian Public Sector Banks - Annapurna, V.; Manchala, G. (Indian Journal of Finance, 2017)
This study used the balanced scorecard (BSC) concept developed by Kaplan and Norton (1992). The empirical study evaluated the performance of top three public sector banks in India namely, State Bank of India, Bank of Baroda, and Punjab National Bank using the balanced scorecard framework developed for these banks. Further, profitability of these banks during the period from 2006 - 2015 was measured in terms of return on assets (RoA) and return on equity (RoE). In addition, this paper also examined the relationship between profitability and variables in the BSC framework using correlation and multiple regressions. The results revealed variance in the performance of the three banks in balanced scorecard perspectives. The outcomes also disclosed statistically significant relationship of the variables - capital adequacy ratio, net non-performing assets ratio, number of ATMs, and number of skilled employees with RoA. The variables - capital adequacy ratio, net non-performing assets ratio, number of ATMs, number of skilled employees, and ratio of wage bills to total income disclosed statistically significant relationship with RoE. The results of regression analysis revealed the variable - net non-performing assets ratio had a significant direct linear relationship with RoA. On the other hand, the variable - capital adequacy ratio was found to have a direct relationship and net non-performing assets ratio had an inverse relationship with RoE.